Integrated computational framework for the design and fabrication of bending-active structures made from flat sheet material. (December 2021) - Laccone, Francesco; Malomo, Luigi; Pietroni, Nico; Cignoni, Paolo; Schork, Tim
Graphical abstract: Highlights: Method for the automatic design of bending-active structures from an arbitrary shape. The FlexMaps algorithm is modified and extended at the architectural scale. Automated shape-to-factory workflow for advanced manufacturing. Application in a 1:1 scale proof of concept demonstrator. Abstract: This paper introduces an integrated computational design framework for the design and realization of arbitrarily-curved bending-active architectural structures. The developed framework consists of a series of methods that enable the production of a complex 3D structures composed of a set of flat 2D panels whose mechanical properties are locally tuned by varying the shape of embedded spiraling patterns. The resulting panels perform as variable stiffness elements, and they are optimized to match a desired target shape once assembled together. The presented framework includes all the steps for the physical delivery of architectural objects, including conception, static assessment, and digital fabrication. The developed framework has been applied to an architectural scale prototype, which demonstrates the potential of integrating architectural design, computational simulation, structural engineering, and digital fabrication, opening up several possible novel applications in the building sector.